Outcome after Translabyrinthine Surgery for Vestibular Schwannomas: Report on 1244 Patients - Springborg, Jacob Bertram; Fugleholm, Kåre; Poulsgaard, Lars; Cayé-Thomasen, Per; Thomsen, Jens; Stangerup, Sven-Eric (Journal of Neurological Surgery Part B: Skull Base, 2012)
The objective of this article is to study the outcome after translabyrinthine surgery for vestibular schwannomas, with special focus on the facial nerve function. The study design is a case series from a national centralized database and it is set in two University Hospitals in Denmark. Participants were 1244 patients who underwent translabyrinthine surgery during a period of 33 years from 1976 to 2009. Main outcome measures were tumor removal, intraoperative facial nerve preservation, complications, and postoperative facial nerve function. In 84% patients, the tumor was totally resected and in ~85% the nerve was intact during surgery. During 33 years, 12 patients died from complications to surgery and ~14% had cerebrospinal fluid leakage. Before surgery, 74 patients had facial paresis and 46% of these improved after surgery. In patients with normal facial function, overall ~70% had a good outcome (House-Brackmann grade 1 or 2). The chance of a good outcome was related to tumor size with a higher the chance the smaller the tumor, but not to the degree of tumor removal. In ~78% of the patients with facial paresis at discharge the paresis improved over time, in ~42% from a poor to a good function. The translabyrinthine approach is generally efficient in tumor control and with satisfactory facial nerve outcome. With larger tumors the risk of a poor outcome is evident and more data on patients managed with alternative strategies are warranted.
Keywords: vestibular schwannoma; translabyrinthine surgery; outcome; facial nerve